PINTU TERLARANG: POTRET MANUSIA SAKIT (Pintu Terlarang: Figure of Human Being) - Resti Nurfaidah (Balai Bahasa Sulawesi Selatan, 2009)
Reading Pintu Terlarang by Asmara is simply like seeing through the deepest base of human illness. We found some abnormal sickness behind the soul of the body. We found so many disasters behind the most faboulous and glamorous performances. This asked us to explore the deepest of the darkness lifestyle of the ‘haves’. The ‘haves’ who are truly have nothing inside the body and the soul. The ‘haves’ who only left the great scratches over the surface of the human civilization. Pintu Terlarang asks us to be the wisest judged of being a human, a wife, a husband,a friend, a bestfriend, a neighbour, a brother, a sister, a mother, a father, or a child. It reflects us that the early sin will be the latest and the biggest at the end. Caring of the bad seed will grow the horrible monsters in the future. Children who had bad growing experiences in their first ages always remember those scratches in their grown upness.